Celebrating Juneteenth - Lynch, Seth (Celebrating our holidays (Cavendish Square Publishing LLC), 2023)
Explores the history and traditions of Juneteenth, and explains how it became a national holiday. Includes color photographs, sidebars, an activity, a glossary, and additional resources.